The invasin D protein from Yersinia pseudotuberculosis selectively binds the Fab region of host antibodies and affects colonization of the intestine - Sadana, Pooja (J Biol Chem, 2018)
Yersinia pseudotuberculosis is a Gram-negative bacterium and zoonotic pathogen responsible for a wide range of diseases, ranging from mild diarrhea, enterocolitis, lymphatic adenitis to persistent local inflammation. The Y. pseudotuberculosis invasin D (InvD) molecule belongs to the invasin (InvA)-type autotransporter proteins, but its structure and function remain unknown. In this study, we present the first crystal structure of InvD, analyzed its expression and function in a murine infection model, and identified its target molecule in the host. We found that InvD is induced at 37 °C and expressed in vivo 2–4 days after infection, indicating that InvD is a virulence factor. During infection, InvD was expressed in all parts of the intestinal tract, but not in deeper lymphoid tissues. The crystal structure of the C-terminal adhesion domain of InvD revealed a distinct Ig-related fold that, apart from the canonical β-sheets, comprises various modifications of and insertions into the Ig-core structure. We identified the Fab fragment of host-derived IgG/IgA antibodies as the target of the adhesion domain. Phage display panning and flow cytometry data further revealed that InvD exhibits a preferential binding specificity toward antibodies with VH3/VK1 variable domains and that it is specifically recruited to a subset of B cells. This finding suggests that InvD modulates Ig functions in the intestine and affects direct interactions with a subset of cell surface-exposed B-cell receptors. In summary, our results provide extensive insights into the structure of InvD and its specific interaction with the target molecule in the host.